2018
DOI: 10.1186/s13018-018-0890-2
|View full text |Cite
|
Sign up to set email alerts
|

New fixation approach for transverse metacarpal neck fracture: a biomechanical study

Abstract: BackgroundFifth metacarpal neck fracture, also known as boxer’s fracture, is the most common metacarpal fracture. Percutaneous Kirschner-wire (K-wire) pinning has been shown to produce favorable clinical results. However, the fixation power of K-wires is a major concern. Plate fixation is also a surgical option, but it has the disadvantages of tendon adhesion, requirement of secondary surgery for removal of the implant, and postoperative joint stiffness. A fixation method that causes little soft tissue damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 38 publications
0
29
2
Order By: Relevance
“…The surgical approach, as well as the reduction and fixation method, is an important factor to consider in the surgical treatment of hand fractures, as the extent of skin and soft tissue incision and periosteal and peritendinous dissection can be affected by the surgical approach [ 4 , 11 ]. According to the literature on surgical approaches, the internal plate fixation method seems to exhibit superior strength to the external pin fixation method [ 12 ]. However, as open reduction and internal fixation involves a skin incision and peritendinous dissection, care should be taken to minimize tissue damage during the incision and dissection, and some surgeons prefer less invasive surgical methods for this reason.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach, as well as the reduction and fixation method, is an important factor to consider in the surgical treatment of hand fractures, as the extent of skin and soft tissue incision and periosteal and peritendinous dissection can be affected by the surgical approach [ 4 , 11 ]. According to the literature on surgical approaches, the internal plate fixation method seems to exhibit superior strength to the external pin fixation method [ 12 ]. However, as open reduction and internal fixation involves a skin incision and peritendinous dissection, care should be taken to minimize tissue damage during the incision and dissection, and some surgeons prefer less invasive surgical methods for this reason.…”
Section: Discussionmentioning
confidence: 99%
“…According to the experimental results, the coefficients of variation for the LP, RP, and K groups were all approximately 30%. These coefficients were higher than those of our previous study, in which artificial bones were employed to investigate the stability of the three fixation methods in metacarpal neck fractures [ 34 ]. This may have been because of differences between the porcine metacarpal specimens.…”
Section: Discussionmentioning
confidence: 56%
“…Because fresh cadaver metacarpals are difficult to obtain, some scholars have used artificial bones for testing [ 32 34 ]. Although the use of artificial bones means that each bone specimen has the identical shape and material properties, artificial bones cannot replicate the trabecular bone structure and anisotropic properties found in actual bones.…”
Section: Discussionmentioning
confidence: 99%
“…From the biomechanical perspective, using only K-wires for fixation is associated with unsatisfactory bending and torque forces [ 11 ]. Nonetheless, numerous studies have reported lower incidences of extensor tendon adhesions and metacarpophalangeal joint stiffness with K-wire fixation than with plate fixation [ 15 , 16 ]. In an effort to retain its strengths and compensate for its disadvantages, the present study developed a new fixation approach involving the placement of two K-wires and figure-of-eight cerclage wire.…”
Section: Introductionmentioning
confidence: 99%
“…Internal fixation with K-wires is frequently used to treat metacarpal shaft fractures, but their lack of functional stability may result in fixation failure. In our previous study, [ 15 ] achieved satisfactory outcomes in the placement of two K-wires and figure-of-8 cerclage wire for the fixation of metacarpal neck fractures. The objective of the present study was to evaluate the effect of incorporating a figure-of-eight cerclage wire with two K-wires on fixation strength for transverse metacarpal shaft fractures.…”
Section: Introductionmentioning
confidence: 99%